The role of public opinion in Africa's third term bids - Mughogho, Dangalira (Department of Political Studies, 2015)
In this paper we show that public opinion variables have predictable effects on the outcomes of the third term bids that have occurred in the post-transition period in Africa. We focus on three public opinion variables that we believe to be critical in explaining variation across these outcomes: popular opposition to authoritarian rule, presidential popularity, and popular trust in the president.